The Application of Ice Breaking in Reducing Student Boredom During Class Learning - Amalia Wulansari; Bagus Rahmad Wijaya; Suyati Suyati (Universitas Trunojoyo Madura, 2026)
This study aimed to examine the implementation of ice-breaking actIities in reducing students' boredom during classroom learning. Using a descriptIe qualitatIe approach, data were collected through interviews, observations, and documentation at SDN Tanah Kalikedinding II/252. The research subjects included one fourth-grade teacher and six fourth-grade students. The results showed that ice-breaking actIities helped create a more enjoyable learning atmosphere and increased students’ focus and motIation. The teacher implemented various types of ice-breaking, such as motIational claps, educational songs, light games, and simple movement exercises. Students responded positIely, expressing that they felt more enthusiastic and less bored during lessons. However, the teacher encountered challenges in choosing appropriate ice-breaking methods and allocating time effectIely for their application. In conclusion, ice-breaking can be considered an effectIe strategy to reduce boredom and support successful learning in primary education.